Enhancing Children's Understanding of Geometric Shapes Through Realia Media - Hayati, Zikra; Munawwarah, Munawwarah; Jarmita, Nida; Hanum, Rafidhah; Hijriati, Hijriati; Masthura, Inayah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Based on the results of initial observations at UPTD SPF PAUD, there are still some children who are mistaken in pronouncing and differentiating each geometric shape. This research aims to determine the use of realia media in increasing children aged 5-6 years' understanding of geometric shapes at UPTD SPF Aceh Singkil. The method used in this research is quantitative with the type of Pre-Experimental Design with a One Group Pretest-Posttest Design. The research results showed that the pretest value was 5.21 and the posttest value was 10.57. Based on the results of hypothesis testing using the Paired Sample-t Test technique, the value obtained at sig. (2-tailed) is 0.000 < 0.05, which means Ha is accepted and Ho is rejected. So it can be concluded that realia media increases the understanding of children aged 5-6 regarding geometric shapes at UPTD SPF PAUD Aceh Singkil.